ASAS KESEIMBANGAN DALAM PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM DENGAN PEMBERIAN GANTI UNTUNG - Heri Suherman; Martin Roestamy (JURNAL ILMIAH LIVING LAW, 2018)
Development for public interest requires the land for which the procurement is carried out by promoting the principles contained in the 1945 Constitution of the State of the Republic of Indonesia and national land law, including humanitarian principles, justice, benefit, certainty, openness, agreement, participation, welfare, sustainability , and alignment in accordance with the values of nation and state. Land acquisition for Ciawi and Sukamahi Dam Projects implemented by the Government, in fact resulted in compulsion, where the Government was forced to buy the land due to the program and so the landowner had to relinquish the land for the program's interest. However, in principle, the procurement of the land must continue to benefit the community as the owner of the land affected by the development program of public interest by applying the balance principle in the provision of compensation that is economically and socially more profitable to realize a sense of justice, improve the standard of living and welfare of affected people Ciawi and Sukamahi dam in Bogor Regency.